Ameliorative Role of Nutraceutical Quercetin and its Derivatives Against Cognitive Impairment Process Induced by Lead Exposure in Drosophila melanogaster(Fruit Fly) - Katsayal, B. S.; A. Lema, A.; Jibrin, K.; Nuraddeen, W.; M. Alexander, E.; Mohammed, N.H (Iraqi Journal of Pharmaceutical Sciences, 2021)
Cumulative lifetime lead (Pb) exposure has been associated with accelerated declines in cognition through the free radical generation and epigenetic effects. Several pieces of literature have identified a correlation between exposure to lead and neurodegenerative disorders. Harwich strain Drosophila melanogaster was exposed to lead acetate for two weeks, and changes in pulse transmission by acetylcholinesterase and systemic redox were evaluated. Besides, molecular docking studies of acetylcholinesterase against Quercetin and its most common derivatives contained in food have been performed. Pharmacokinetic studies on Quercetin and its derivatives have also been performed in silico toxicity. The data obtained showed alterations in antioxidant enzymes and molecules such as catalase, glutathione-S-transferase, and glutathione. Upregulation of acetylcholinesterase activity was observed after treatment with Quercetin. In molecular docking tests, Quercetin and its derivatives were found to bind to acetylcholinesterase’s active and peripheral pockets. Pharmacokinetic studies demonstrate moderate solubility, high therapeutic index, excellent absorption potential, hepatoprotective and non-mutagenic properties. With other antioxidant molecules, Quercetin may also play a crucial role in avoiding the development of Alzheimer’s and associated antioxidant disorders.